Purposeful Play: Women Radio Artists in Canadian Campus and Community Radio - Waterman, Ellen (Atlantis, 2006)
Studies show that women are under-represented in Canadian campus and community radio. Based on ethnographic research and survey data, this article posits a theory of "purposeful play," a set of strategies employed by women radio artists to create community and find their voices on the air.